2006
DOI: 10.1007/s11743-006-5015-y
|View full text |Cite
|
Sign up to set email alerts
|

Surface activity of mixtures of dodecyl trimethyl ammonium bromide with sodium perfluorooctanoate and sodium octanoate

Abstract: In this study, the surface tension of mixtures of cationic surfactant dodecyl trimethylammonium bromide (DTAB) and anionic surfactant sodium perfluorooctanoate (SPFO) was evaluated as a function of DTAB‐SPFO composition and total surfactant concentration, with and without added electrolyte. It was found that the critical micelle concentration (CMC) of these mixtures was reduced by more than two orders of magnitude when compared to the CMC of SPFO and DTAB alone. The surface tension, after CMC, of the mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 20 publications
(37 reference statements)
1
10
0
Order By: Relevance
“…With the addition of oppositely charged ionic surfactant into cationic or anionic surfactant, the strong electrostatic attraction between the oppositely charged headgroups takes the place of the electrostatic repulsion between the same charged headgroups, it is in favor of the reduction of the distance between the headgroups and the strengthening of the interaction between the surfactant molecules, thus it promotes the aggregation of the surfactant molecules at the air/solution interface and the formation of micelles, leading to the increase of cmc , and the decrease of cmc, cmc and A min . [66,67] illustrate that the surface tensions after cmc are the same within a wide composition range. For the 12-3-12 2+ ·2Br − /Y + AS − /H 2 O systems with different Y + ions, the surfactant cations and surfactant anions are the same, the monolayer at the air/solution interface is composed by the complex salt 12-3-12 2+ ·2AS − , meanwhile, the monolayer is located at the 'gas'-'liquid' coexisted region, thus these mixed systems with different Y + ion and different compositions give almost the same ˘c mc and cmc values.…”
Section: Mixed Micellization Of 12mentioning
confidence: 91%
See 2 more Smart Citations
“…With the addition of oppositely charged ionic surfactant into cationic or anionic surfactant, the strong electrostatic attraction between the oppositely charged headgroups takes the place of the electrostatic repulsion between the same charged headgroups, it is in favor of the reduction of the distance between the headgroups and the strengthening of the interaction between the surfactant molecules, thus it promotes the aggregation of the surfactant molecules at the air/solution interface and the formation of micelles, leading to the increase of cmc , and the decrease of cmc, cmc and A min . [66,67] illustrate that the surface tensions after cmc are the same within a wide composition range. For the 12-3-12 2+ ·2Br − /Y + AS − /H 2 O systems with different Y + ions, the surfactant cations and surfactant anions are the same, the monolayer at the air/solution interface is composed by the complex salt 12-3-12 2+ ·2AS − , meanwhile, the monolayer is located at the 'gas'-'liquid' coexisted region, thus these mixed systems with different Y + ion and different compositions give almost the same ˘c mc and cmc values.…”
Section: Mixed Micellization Of 12mentioning
confidence: 91%
“…Usually the micellar compositions of the mixed cationic/anionic surfactants at cmc are nearly equimolar over a wide range of mixing ratios [46][47][48][49], the addition of inorganic salt has little or no effect on the cmc of these mixed cationic/anionic surfactant systems. While only for those aqueous mixed cationic/anionic surfactants far from equimolar ratio, the addition of salt reduces the mixed cmc in different extents, and the reduction degree increases when the composition deviates further away from equimolar ratio.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, due to the high surfactant content, the combination of the prepared CNT dispersions with the polymer matrices alters the processability of the resulting system and further optimization of the composite material is usually required. Acosta et al [20] proposed the use of mixtures of anionic surfactants with cationic surfactants for improving the efficiency of the surfactants, and subsequent studies [21,22] showed special synergism between anionic/cationic surfactants, which reduced the concentration of surfactant required to disperse CNTs. However, to the best of our knowledge, no preparation of composite materials with mixed surfactant CNT dispersions has been published.…”
Section: Introductionmentioning
confidence: 99%
“…This also implied the existence of synergistic interaction for the mixed surfactant CTAB-TX100. It has been reported that for ionic-nonionic mixed surfactant systems, the synergistic nature of the mixture induces a decrease in the CMC owing to the reduction in electrical repulsion between ionic heads of the original ionic surfactant as well as mixed micelle formation between the ionic and nonionic surfactant [18]. The reduction in CMC helps to disperse MWNT at lower total surfactant concentration as compared to the individual surfactants used alone.…”
Section: Resultsmentioning
confidence: 99%